2021
DOI: 10.7150/ijbs.64003
|View full text |Cite
|
Sign up to set email alerts
|

CDC20 regulates the cell proliferation and radiosensitivity of P53 mutant HCC cells through the Bcl-2/Bax pathway

Abstract: Purpose: The incidence of hepatocellular carcinoma (HCC) is extremely high, and China accounts for approximately 50% of global liver cancer cases. Previous studies reported that CDC20 is involved in the occurrence and progression of a variety of malignant tumors. So, whether CDC20 will affect the development of HCC, we have conducted in-depth research on this. Methods: We selected Hep3B and HepG2 for cell culture, and performed siRNA transfection, lentiviral infection, wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 34 publications
0
34
0
Order By: Relevance
“…For instance, CDC20 was reported to be highly increased and served as an unfavorable prognosis marker in HCC samples. Knockdown of CDC20 noticeably promoted the radiation efficacies on the growth retardation in HCC cells via regulating Bcl-2/Bax signal, and the expressions of CDC20 were noticeably reduced due to the overexpression of P53 through radiation [ 26 ]. Yu et al reported that E2F1, which was highly expressed in HCC, mediated DDX11 transcriptional activation facilitates HCC cells' invasion, migration, and proliferation via PI3K/AKT/mTOR pathway [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, CDC20 was reported to be highly increased and served as an unfavorable prognosis marker in HCC samples. Knockdown of CDC20 noticeably promoted the radiation efficacies on the growth retardation in HCC cells via regulating Bcl-2/Bax signal, and the expressions of CDC20 were noticeably reduced due to the overexpression of P53 through radiation [ 26 ]. Yu et al reported that E2F1, which was highly expressed in HCC, mediated DDX11 transcriptional activation facilitates HCC cells' invasion, migration, and proliferation via PI3K/AKT/mTOR pathway [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…CDC20 has been also involved in the apoptotic response, by regulating phosphatidylcholine (PC) cycle [ 102 , 103 ] and balancing the activity of anti-apoptotic factors, as MCL-1 [ 104 108 ] and BCL-2 [ 108 , 109 ], and pro-apoptotic factors, as BIM [ 110 ] (Fig. 5 A-D).…”
Section: Main Textmentioning
confidence: 99%
“…CDC20 is overexpressed in tumor cells and acts as a poor prognostic factor in multiple cancers (63,64). It further increased after radiation and has been reported to increase radiation resistance via regulating B-cell lymphoma-2 (Bcl-2)/Bcl-2-associated X protein (Bax), forkhead box proteins O1 (FoxO1), or myeloid cell leukemia sequence 1 (Mcl-1)/p-CHK1 in different cancer types (65)(66)(67). Suppression of CDC20 expression reverses the radioresistance (65)(66)(67).…”
Section: Cdc20mentioning
confidence: 99%